A Systemic Review Of Ilio Tibial Band Syndrome With Its Ayurved Treatment Perspective - Akhila , A R; Sharma, Vishnu Dutt; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Iliotibial band syndrome/ilio tibial band friction syndrome is one among the 3 common pathological conditions of knee joint like ITBS, Chondromalacia patella, & OA knee. Knee joint is the most complex joint in human system which undergoes continuous wear & tear, while trying to stabilize during various activities. This continuous wear & tear results in knee pain which ranges from minor to unbearable morbidity. As the knee joint is the constant pressure joint, it facilitates the pathology to manifest easily. ITBS is the 2nd most common knee related pain which affects runners after patello-femoral dysfunction. Also, it is the common injuries of lateral side of knee in athletes mainly runners with an incidence estimated to be between 5% and 14%. Now a days, this morbidity has emerged in the front line among sports population & so further studies are needed for fruitful outcome. Ayurvedic science can impart a huge result in the area of sports medicine likewise in ITBS. Various Bheshaja chikitsa (treatment through medicines) and some of the para surgical procedures can be applied for patient satisfaction and thereby can reduce the morbidities associated with the same.